Art and architecture in Neolithic Orkney : process, temporality and context - Thomas, Antonio, (University of the Highlands and Islands Archaeology Institute research series ;, 2016)
This text offers a groundbreaking analysis of Neolithic art and architecture in Orkney, focusing upon the incredible collection of hundreds of decorated stones being revealed by the current excavations at the Ness of Brodgar.